Synthesis and structure-properties relationships of small organic fluorophores - Vaz, Patrícia Alexandra Amaro Martins (2024)
Luminescent small organic molecules, in particular fluoroborates complexes, have attracted significant attention in recent years due to their potential optoelectronic and biological applications. Organic solid-emissive dyes are scarce because most undergo self-quenching in concentrated solution or in solid state. The aggregation-induced emission enhancement (AIEE) effect has been much explored to improve luminescence in solid state, where chromophores poorly emissive in dilute solution become highly fluorescent or phosphorescent in the solid state. The restriction of intramolecular rotations (RIR) has been proposed as the main cause for the enhanced solid-state emission. In search for efficient all-organic solid-state luminophores, halogen bonding (XB) has emerged as an important factor that promotes inter-system crossing through the heavy atom effect and thus induces phosphorescence emission. This work presents our strategy to develop new luminescent small organic materials molecules as promising blue-emitting solid materials combining the XB and AIEE effect and proposing structural modifications in some fluoroborates complexes to minimize the effects of intramolecular rotations (IR) in solid state. We discuss the synthesis and study of different families of organic dyes (chalcone, benzophenone and benzimidazole derivatives) decorated with halogen atoms as wells as fluoroborates complexes with structural features suitable to produce blue-emitting solid materials. The ligand-boron complexation, the occurrence of halogen bonding, the complementarity or competition with hydrogen bonding, their importance for the organization of the compounds in the crystal packing and influence on the luminescence properties are presented and discussed. This work resulted in the synthesis, characterization, and optoelectronic study of new pure blue luminescent organic compounds in solution and in solid state with potential to be used in optical.